If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 17 + -3X = 11 Reorder the terms: 17 + X + -3X = 11 Combine like terms: X + -3X = -2X 17 + -2X = 11 Solving 17 + -2X = 11 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + -2X = 11 + -17 Combine like terms: 17 + -17 = 0 0 + -2X = 11 + -17 -2X = 11 + -17 Combine like terms: 11 + -17 = -6 -2X = -6 Divide each side by '-2'. X = 3 Simplifying X = 3
| 227-5x=81+19 | | 3x+38=11x-26 | | (-5)x=-(-10) | | 0.4-1.2=0.3+0.6 | | q+16=-3 | | x-(-37)=55 | | 3ln(2)-2ln(3)=0 | | 48=-4(-3x-6) | | -14=a+24 | | x=3r-12 | | 2(2n+3)=10 | | (-1)x=-10 | | 5x^2+24x+27=0 | | m-16=8 | | 3+3r-4r=-1 | | 3(10-2n)=0 | | 8+y=-7 | | 1.4f+1.1=8.3f | | 26y=32 | | 1.4f+1.1=8.3f | | 2x=-(-8) | | r^2+2r+2=0 | | 4.8=-16+1.6z | | 5(2n+1)=25 | | 0.75w+4=-3(0.75w+2)+8 | | 6x-2(x-2)=9x+4 | | (-2)x=-5 | | 6a^2-13a+5=0 | | -3.8d=8.74-1.9d | | x-(-6)=-80 | | 10(n-2)=100 | | -22=r+3+4r |